The molecular prevalence of Theileria equi in the Arabian stallion in Egypt with special reference to biochemical parameters - Noora F. Thabet; Omaima M. Kandil; Omnia M. Kandil; Khalid M. Fararh (Iraqi Journal of Veterinary Sciences)
Theileria equi, a blood parasite spread by ticks, is thought to be a severe infectious disease that impacts the health of horses. The study's main goal was to determine the prevalence of T. equi in Arabian stallions in Egypt by comparing microscopic examination (ME) and conventional polymerase chain reaction (cPCR) and compare them. The study aimed to determine the liver and kidney functions of infected Arabian stallions with T. equi. Out of the 100 Arabian stallions in Egypt tested for T. equi infection, only 30 (30%) were positive through microscopic analysis, and 38(38%) were positive through a cPCR test. Arabian stallions were divided into two groups: the first group, positive T. equi infection (infected group) (n = 30). In the second group, negative T. equi infection (healthy group) (n = 10) and liver and kidney function were detected for both groups. Serum analysis revealed significant changes in the infected group's liver and kidney function parameters. Total bilirubin, direct bilirubin, indirect bilirubin, GGT, GOT (AST), urea, and creatinine were significantly increased in the serum of the infected group compared with the healthy group; total protein, albumin, and globulin were found to be decreased in the serum of the infected group when compared to the healthy group. The ALP and albumin: globulin (A: G) ratio changes weren’t significant in this study. Studying the molecular prevalence of T. equi in the Arabian stallion in Egypt with special reference to biochemical parameters will help evaluate the prognosis and treatment of theileriosis.